Proton induced radiation damage studies on plastic scintillators for the tile calorimeter of the atlas detector - Jivan, Harshna (My University, 2016)
Plastic scintillators play a key role in reconstructing the energy and tracks of hadronic particles that impinge the Tile Calorimeter of the ATLAS detector as a result of high energy particle collisions generated by the Large Hadron Collider of CERN. In the detector, plastic scintillators are exposed to harsh radiation environments and are therefore susceptible to radiation damage. The radiation damage effects to the optical properties and structural damage were studied for PVT based commercial scintillators EJ200, EJ208, EJ260 and BC408, as well as PS based UPS923A and scintillators manufactured for the Tile Calorimeter. Samples of dimensions 5x5x0.3 mm were subjected to irradiation using 6 MeV protons to doses of approximately 0.8 MGy, 8 MGy, 25 MGy and 25 MGy using the 6 MV tandem accelerator of iThemba LABS. Results show that damage leads to a reduced light output and loss in transmission character. Structural damage to the polymer base and the formation of free radicals occur for doses ≥ 8 MGy leading to reduced scintillation in the base and re-absorption of scintillation light respectively. Scintillators containing a larger Stokes shift, i.e. EJ260 and EJ208 exhibit the most radiation hardness. EJ208 is recommended as a candidate to be considered for the replacement of Gap scintillators in the TileCal for the 2018 upgrade.
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2016.
Keywords: Scintillators; Calorimeters; Large Hadron Collider (France and Switzerland); Particle accelerators